Preparation and characterization the microstructure and the surface area of magnesium oxide nanoparticles - Jadoo, Shaimaa A.; Fendi, Wedad J.; Naser, Juman A.; Jamur, Jasim M. S. (Iraqi Journal of Science, 2026)
Magnesium oxide nanoparticles were synthesized via a co-precipitation procedure. Comprehensive characterization included infrared fluorescence, X-ray scattering spectroscopy, scanning electron microscopy, as well as X-ray diffraction and atomic force microscopy. Surface properties were analyzed using Langmuir, Brunauer -Emmett-Teller, Barrett–Joyner–Halenda, t-plot techniques, and the N2 adsorption-desorption isotherms methods to determine surface area and pore structure. Results confirmed the nanoparticles possess high purity. The size of the synthesized particles ranged from 30-40 nm, which was determined by scanning electron microscopy. The surface area of the prepared particles is 31,227 m2 g-1, and it was found that the pore volume was 0.03031 cm3 m-1, while the pore diameter was 1.21 nm.